Misoprostol (PGE1) versus dinoprostone gel (PGE2) in induction of labour in late intra uterine fetal death with unfavourable cervix: a prospective comparative study - Biswas, Titol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to compare the efficacy, safety and tolerance of misoprostol versus dinoprostone gel in induction of labour in the case of late Intra Uterine Fetal Death (IUFD) with unfavourable cervix. Methods: This prospective study included a consecutive series of 40 women gravid up to fourth with IUFD after 28 weeks of gestation between March 2013 to Feb 2014. Women were divided into two groups. Each group consisted of 20 women. First group of women received 100 μg of misoprostol per vaginally at four hourly intervals (maximum 600 μg in 24 hours). Second group of women received dinoprostone gel 0.5 mg intracervically at every 6 hours, maximum 2 doses in 24 hours. Oxytocin was given for augmentation if needed. Results: The induction-to-delivery interval was significantly shorter with the misoprostol (8.13 ± 1.62 hours vs. 14.32 ± 2.46 hours; P <0.001) group. The total dose of misoprostol needed was significantly lower than the group pre-treated with dinoprostone gel (1.78 ± 0.80 vs. 3.50 ± 1.12; P <0.001). The two groups did not differ as regards complications experienced during labour and delivery significantly. Conclusions: Both regimens, misoprostol and dinoprostone are safe in induction of labour after intrauterine fetal death (IUFD). Misoprostol is more effective in terms of reducing of induction delivery interval, requirement of lesser dose.